Respuesta :

10n31y

[tex] {a}^{2} + {b}^{2} = {c}^{2} [/tex]

[tex] {c}^{2} - {b}^{2} = {a}^{2} [/tex]

[tex] {8}^{2} - {6}^{2} = {28}^{2} [/tex]

[tex] \sqrt{28} [/tex]

Answer:

[tex]\boxed{\sf{a=\sqrt{28} }}[/tex]

Step-by-step explanation:

Pythagorean theorems can be applied to solve this problem.

Pythagorean theorem:

[tex]\rightarrow \sf{a^2+b^2=c^2}[/tex]

⇒ c²-b²=a²

8²-6²=28²

Solve.

PEMDAS stands for:

  • Parenthesis
  • Exponents
  • Multiply
  • Divide
  • Add
  • Subtract

[tex]\sf{8^2-6^2}[/tex]

Solve by exponents from left to right numbers.

[tex]\sf{8^2=8*8=64}[/tex]

[tex]\sf{6^2=36}[/tex]

Then, subtract.

[tex]\sf{64-36=\boxed{\sf{28}}[/tex]

a=√28

Therefore, the correct answer is a=√28.

I hope this helps you! Let me know if my answer is wrong or not.